Statistical modelling optimisation of cellulase enzyme immobilisation on functionalised multi-walled carbon nanotubes for empty fruit bunches degradation - Al-Khatib, Ma An Fahmi Rashid; Alam, Md Zahangir; Mohammed, Rasha (INSINET PUBL, 2012)
Cellulase obtained from the fermentation of sewage treatment plant sludge (STP) by Trichoderma-reesei RUT C-30 was covalently immobilised on functionalised multi-wall carbon nanotubes. Statistical optimisation using the Plackett–Burman design method was implemented to identify parameters with significant effects on the process of immobilisation. The results obtained from this Plackett–Burman design show that three parameters have a significant effect on immobilisation: pH, temperature, and N-ethyl-N-(3-dimethyl aminopropyl) carbodiimide hydrochloride (EDC) concentration. Based on our Plackett-Burman design results, these parameters were further optimised using a face-centred central composite design. The resulting optimum conditions for cellulase immobilisation, as determined by face-centred central composite design, were pH 4.5, 30°C, and 1 mL of 10mg/mL EDC. The amount of immobilised cellulase was approximately 98% using these optimum conditions. The resulting MWCNT-cellulase composite was further characterized by FTIR and SEM. The FTIR spectrum of MWCNT-cellulase composite showed an amide group peak (O = C-NH) corresponding to cellulase enzyme, which confirms that immobilisation took place.